Tracing bank runs in real time - Marco Cipriani; Thomas M. Eisenbach; Anna Kovner (Federal Reserve Bank of New York, 2024)
We use high-frequency interbank payments data to trace deposit flows in March 2023 and identify twenty-two banks that suffered a run - significantly more than the two that failed but fewer than the number that experienced large negative stock returns. The runs were driven by large (institutional) depositors, rather than many small (retail) depositors. While the runs were related to weak fundamentals, we find evidence for the importance of coordination because run banks were disproportionately publicly traded and many banks with similarly bad fundamentals did not suffer a run. Banks that survived a run did so by borrowing new funds and then raising deposit rates - not by selling liquid securities.
Keywords: E41; E58; G01; G21; G28; 330; bank runs; payments; coordination; public signals